The Influence of Forced and Natural Convection on the Sensory Characteristics of Dried Fish - Rizkia; Ahmad Syuhada (International Journal of Marine Engineering Innovation and Research, 2024)
Indonesia is one of the countries with the largest archipelagos in the world, boasting an abundant wealth of natural biodiversity. One of these resources is fisheries. The production of dried fish is one of the community's efforts to increase the selling price of fish. The dried fish produced by the community is usually sold in traditional markets and has few buyers due to the lack of attention to the quality of the dried fish. To increase buyers' interest in dried fish, the quality must be improved. The aim of this study is to enhance the production system and quality of dried fish through the use of drying equipment with different drying methods, namely natural convection and forced convection drying systems. In natural convection, the drying process utilizes the movement of air flows caused by density differences, while in forced convection drying, the air flow rate is controlled with the help of a fan. This study involves the use of four variations of air velocity that will be tested: 1 m/s, 2 m/s, 3 m/s, and a gradual reduction from an initial speed of 3 m/s, decreasing by 1 m/s every 3 hours of drying until reaching 1 m/s. Drying is then continued at an air flow rate of 1 m/s until the desired moisture content is achieved. The results of the study indicate that the use of natural convection and forced convection drying methods affects the drying rate and the final product quality, including color, texture, and taste. From the results obtained, the use of forced convection drying method with a gradual reduction in air velocity proved to be the best treatment, with a drying rate of 0.036 kg/h, yielding the best final quality in terms of color, texture, and taste.